Effects of Possible Osteoporotic Conditions on the Recurrence of Chronic Subdural Hematoma - Ha, Byeong Jin; Bae, In-Suk; Kim, Jae Min; Cheong, Jin Hwan; Ryu, Je Il; Han, Myung-Hoon (Frontiers in Neurology, 2020)
The recurrence rate of chronic subdural hematoma (CSDH) has been reported to range from 2.3% to 33%. As bridging veins are composed of abundant collagen bundles and bone matrix, we aimed to investigate the possible associations between skull Hounsfield unit (HU) values and the recurrence of CSDH. We retrospectively enrolled patients with CSDH who underwent burr hole surgery. The HU values of the frontal skull were measured on brain CT scans. The cumulative hazard for recurrence was estimated according to predictive factors. To identify the independent predictors associated with the recurrence of CSDH, hazard ratios (HRs) were estimated using multivariate Cox regression analysis. A total of 208 consecutive patients who underwent burr hole trephination for CSDH over a 7-year period at a single institution were enrolled in this study. We found that age, greater midline shift (≥ 10.5 mm), lower skull HU (< 769.5), and diabetes were independent predictors for the recurrence of CSDH (HR 1.06, 95% confidence interval [CI] 1.00–1.12, p = 0.042; HR 5.37, 95% CI 1.48–19.46, p = 0.010; HR 6.71, 95% CI 1.84–24.45, p = 0.004; and HR 3.30, 95% CI 1.05–10.43, p = 0.042, respectively). A relationship between possible low bone mineral density (BMD) and CSDH recurrence was observed. In addition, age, greater preoperative midline shift, and diabetes were also identified as predictive factors for recurrence. We expect that our findings may facilitate our understanding of the possible association between CSDH and BMD.